DEVELOPMENT OF DESIGN PRINCIPLES DROIT DE PREFERENCE AGAINST OWNERS BUSINESS PREMISES IN TANAH ABANG JAKARTA - Ilman Khairi; Abraham Yazdi Martin (JURNAL ILMIAH LIVING LAW, 2017)
Use Rights Certificate Business Place (SHPTU) is proof of ownership of the right to use business premises (shop) in a market that is owned by market traders. SHPTU have a fairly high economic value. Therefore, expected SHPTU can be used as loan collateral. SHPTU have a common element of the lease, as in article 1548 of the Civil Code. Because SHPTU not the right material, then SHPTU can not be guaranteed by using a material guarantee institutions. The research method with the added element of normative juridical empirical, with the analysis of qualitative data. From the analysis it can be concluded that SHPTU not the right material, but given SHPTU has economic value and can be transferred, it is expected that the government can immediately respond to the needs of society (the Merchants Market) to the existence of a guarantee institution which can accommodate SHPTU shop as loan collateral. Resulting from the rigidity of the legal material to deliver the right material on business premises or SHPTU recommended for use kaedah contained in Article 48-49 of the legislation Flats by issuing Certificates of Building Owners and Building (SKBG), where the issuance of the certificate is the same between Local government in this case the Department of Public Works and the Department of Housing, while still managing PD Pasar Jaya as it has been running for this. Issuing authority on the issuance of a certificate is not PD Pasar Jaya but agency in charge of publishing the SKBG. When referring to the Building Act SKBG publishing at the Department of Public Works, and when referring to the Law on Housing, the publishing SKBG by the Department of Housing. That way it is assured of legal certainty as mandated by state law, as well as the grand theory of Hans Kelsen. SKBG is way out proof of ownership of the store, which is very expensive because of the value it needs the necessary legal certainty regarding the right material.Keyword: Droit De’ Preference, UMKM, Shops